A lithium supplement additive and its preparation method and application
By using lithium nitride in pure α crystal phase, pure β crystal phase or mixed crystal phase as lithium supplement additives, and using a simple preparation method, the problem of poor stability of existing lithium supplement additives is solved, and the first charging efficiency and electrochemical performance of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202210254247.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-03-10
AI Technical Summary
The existing lithium supplement additives have poor stability, which leads to unstable granule capacity in lithium-ion batteries, affecting the consistency of battery cell capacity.
Pure alpha crystal phase lithium nitride, pure beta crystal phase lithium nitride or mixed crystal phase lithium nitride composed of alpha crystal phase and beta crystal phase are used as lithium supplement additives, and then grinding is made by calcining the metal lithium in a nitrogen atmosphere.
It improves the battery's first charging efficiency and overall electrochemical performance, ensures that the voltage changes during charging are relatively stable, and enhances the stability of lithium supplement additives.
Smart Images

Figure CN115312771B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion battery additives, and in particular relates to a lithium supplement additive and a preparation method and application thereof. Background Art
[0002] Lithium supplement additives with high specific capacity can form SEI film during the first charge and discharge of lithium-ion batteries, reduce the loss of active lithium in the positive electrode material, and thus improve the battery's first coulombic efficiency and battery capacity. At present, the main methods of lithium supplementation are positive electrode lithium supplementation and negative electrode lithium supplementation. However, the processes of lithium powder spraying, early formation, and adding electrodes to the negative electrode in the negative electrode lithium supplementation technology are demanding on equipment and process technology, and are difficult to be widely used at the current technical level. The positive electrode lithium-rich material lithium supplementation method can achieve pre-lithiation of the negative electrode during the first charge by introducing non-metallic lithium compounds into the positive electrode. However, these non-metallic lithium compounds are unstable in the air and are easily deteriorated by reacting with water vapor and oxygen in the air. For example, lithium nitride prepared by traditional methods has an uncontrollable crystal phase ratio and poor stability. When it is used as a lithium supplement additive combined with the lithium battery preparation process, there will be a problem of unstable gram-specific capacity, which affects the consistency of the battery cell capacity. Therefore, these non-metallic lithium compounds can only be used in an inert environment, which limits large-scale application. Summary of the invention
[0003] The purpose of the present application is to provide a lithium supplement additive and a preparation method and application thereof, aiming to solve the technical problem of poor stability of existing lithium supplement additives.
[0004] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0005] In a first aspect, the present application provides a lithium supplement additive, the lithium supplement additive comprising lithium nitride, wherein the lithium nitride comprises α-crystalline lithium nitride and / or β-crystalline lithium nitride.
[0006] In a second aspect, the present application provides a method for preparing a lithium supplement additive, comprising the following steps:
[0007] Providing lithium metal;
[0008] The metallic lithium is placed in a nitrogen atmosphere for calcination treatment, and then ground to obtain lithium nitride.
[0009] In a third aspect, the present application provides a positive electrode material, which contains the electrode lithium supplement additive provided by the present application or the lithium supplement additive prepared by the preparation method provided by the present application.
[0010] In a fourth aspect, the present application provides a secondary battery, which contains the positive electrode material provided by the present application.
[0011] Compared with the prior art, this application has the following technical effects:
[0012] The lithium supplement additive provided in the first aspect of the present application contains lithium nitride, which is pure α-crystalline lithium nitride or pure β-crystalline lithium nitride or a mixed crystalline lithium nitride composed of α-crystalline and β-crystalline phases. The lithium ion conductivity of pure α-crystalline lithium nitride is high, which is conducive to the release of lithium ions. The lithium ion migration energy barrier of pure β-crystalline lithium nitride is high, and the decomposition voltage is high, which makes the migration of lithium ions in the battery system more stable. The mixed crystalline lithium nitride has reduced activity, which can avoid the reaction with widely used N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in the homogenization process. It has good stability when used. Therefore, when the lithium nitride provided in the present application is used as a lithium supplement additive, the lithium nitride can supplement the lithium ions consumed by the negative electrode to form the SEI film during the first cycle of charging of the battery, so that the lithium ions in the battery system remain abundant, thereby improving the first charging efficiency and overall electrochemical performance of the battery. Therefore, it can ensure that the voltage changes relatively smoothly during the charging process.
[0013] The preparation method of the lithium supplement additive provided in the second aspect of the present application is to calcine the provided metallic lithium in a nitrogen atmosphere, and then grind it to obtain lithium nitride, which can be used as a lithium supplement additive. The preparation process is simple, easy to implement, and has low production cost. In addition, the lithium nitride prepared by the preparation method has good material stability and electrochemical properties, which is conducive to improving the first charging efficiency and overall electrochemical performance of the battery.
[0014] The positive electrode material provided in the third aspect of the present application has material stability and good electrochemical properties, and can ensure that the voltage of the battery changes smoothly during the charging process, because the positive electrode material contains the electrode lithium supplement additive provided by the present application or the lithium supplement additive prepared by the preparation method provided by the present application.
[0015] The secondary battery provided in the fourth aspect of the present application contains the positive electrode material provided in the present application. Therefore, during the first charging process, the lithium replenishing additive contained in the secondary battery of the present application can serve as a lithium source, releasing lithium ions during the first charging process to achieve lithium replenishment, thereby maintaining the abundance of lithium ions in the battery system and improving the battery's first charging efficiency and overall charge and discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 is a flow chart for preparing a lithium supplement additive provided in an embodiment of the present application;
[0018] Figure 2 is the XRD spectrum of the lithium nitride core provided in the embodiment of the present application;
[0019] Figure 3 It is a capacity-voltage diagram of button cells assembled with lithium supplement additives provided in Example 5 and Comparative Example 2 of the present application;
[0020] Figure 4 This is a capacity-voltage diagram of a button cell without adding a lithium supplement additive and with adding the lithium supplement additive provided in Example 3 of the present application to the lithium iron phosphate positive electrode. DETAILED DESCRIPTION
[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0023] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0024] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0026] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0027] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0028] A first aspect of an embodiment of the present application provides a lithium supplement additive, the lithium supplement additive includes lithium nitride, and the lithium nitride includes α-crystalline lithium nitride and / or β-crystalline lithium nitride.
[0029] The lithium supplement additive provided in the embodiment of the present application includes lithium nitride, which is pure α-crystalline lithium nitride or pure β-crystalline lithium nitride or a mixed crystalline lithium nitride composed of α-crystalline and β-crystalline phases. The lithium ion conductivity of pure α-crystalline lithium nitride is high, which is conducive to the release of lithium ions. The lithium ion migration energy barrier of pure β-crystalline lithium nitride is high, and the decomposition voltage is high, which makes the migration of lithium ions in the battery system more stable. The mixed crystalline lithium nitride has reduced activity, which can avoid the reaction with widely used N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) in the homogenization process. It has good stability when used. Therefore, when the lithium nitride provided in the present application is used as a lithium supplement additive, the lithium nitride can supplement the lithium ions consumed by the negative electrode to form the SEI film during the first cycle of charging of the battery, so that the lithium ions in the battery system remain abundant, thereby improving the first charging efficiency and overall electrochemical performance of the battery. Therefore, it can ensure that the voltage changes relatively smoothly during the charging process.
[0030] In an embodiment, the lithium nitride includes α-crystalline lithium nitride and / or β-crystalline lithium nitride, that is, it may include any one of α-crystalline lithium nitride, β-crystalline lithium nitride, and a mixed crystalline lithium nitride composed of α-crystalline and β-crystalline phases. In a specific embodiment, the lithium nitride core may be α-crystalline lithium nitride, β-crystalline lithium nitride, or a mixed crystalline lithium nitride composed of α-crystalline and β-crystalline phases.
[0031] In an embodiment, the lithium nitride includes α-crystalline lithium nitride and β-crystalline lithium nitride, and the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride is (2-10): (90-98) or (70-98): (2-30). Within the range of the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride provided in this embodiment, the stability of the mixed crystalline phase lithium nitride of α-crystalline and β-crystalline is optimal, and the number of lithium ions released from the lithium nitride during the first cycle of charging is the largest, which can optimize the first charging efficiency and overall electrochemical performance of the battery. In a specific embodiment, the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride can be but is not limited to 2:90, 2:92, 2:94, 2:96, 2:98, 6:91, 6:93, 6:95, 6:97, 6:98, 10:90, 10:92, 10:94, 2:96, 2:98, 70:2, 70:10, 70:20, 70:30, 85:2, 85:10, 85:20, 85:30, 98:2, 98:10, 98:20, 98:30.
[0032] In an embodiment, lithium nitride may be a primary particle of lithium nitride, or a secondary particle formed by agglomeration of primary particles. When lithium nitride is a primary particle or a secondary particle, the particle size of lithium nitride is 0.1-50 μm. Preferably, the particle size of lithium nitride is 1-5 μm. The particle size of the specific lithium nitride kernel may be, but is not limited to, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm. Within the particle size range of lithium nitride provided in the embodiment of the present application, the conductivity and stability of the lithium supplement additive can be optimized.
[0033] In an embodiment, the lithium supplement additive further includes a two-dimensional conductive material bonded to the surface of lithium nitride. The two-dimensional conductive material contained in the embodiment of the present application is at least bonded to the surface of lithium nitride. Since the two-dimensional conductive material has good chemical stability and conductivity, bonding to the surface of lithium nitride can improve the stability of the lithium nitride material and increase the conductivity of the lithium supplement additive as a whole, which is conducive to voltage stabilization during the charging process.
[0034] In an embodiment, a two-dimensional conductive material combined with the surface of lithium nitride forms a two-dimensional conductive material coating layer that fully or partially covers lithium nitride. At this point, the lithium supplement additive in the embodiment of the present application constitutes a core-shell structure, the above particle morphology lithium supplement material constitutes a core body, and the two-dimensional conductive material coating layer constitutes a shell layer, at least a part of the shell layer. Among them, the two-dimensional conductive material coating layer can be a fully or partially coated lithium supplement material and also a lithium nitride core body. It is ideal to be fully coated, which can improve the protective effect of the two-dimensional conductive material coating layer on the lithium supplement material, can isolate the lithium nitride kernel from contact with the air, and avoid water, oxygen and carbon dioxide in the air from corroding the lithium nitride kernel, which can improve the stability of the lithium nitride material. In addition, the two-dimensional layered two-dimensional conductive material has the ability to adsorb and desorb various atoms or molecules, which is convenient for adsorbing on the surface of lithium nitride to form a uniform and tight coating layer, which is beneficial to the release of lithium ions during the lithium nitride charging process.
[0035] In an embodiment, the two-dimensional conductive material includes at least one of graphene, graphyne, transition metal disulfide, and MXenes material; wherein the general formula of MXenes material is M n+1 X n T x , M includes at least one of Ti, Cr, Mo, V, Nb, Hf, Ta, and Sc; X includes at least one of C and N; T x Including OH - 、F - , O 2- NH4 + , NH3; n is 1-4. n+ 1X n T x The transition metal disulfide may include but is not limited to at least one of Ti2CO, Ti3C2O, Ti2NO, Ti3N2O, Ti2COH, and Ti3C2OH. The transition metal disulfide may include at least one of MoS2, WS2, SnS2, and TiS2.
[0036] In the embodiment, in the lithium supplementing additive, the mass ratio of lithium nitride to the two-dimensional conductive material coating layer is (9-99): 1. Within the range of the mass ratio of lithium nitride to the two-dimensional conductive material coating layer provided in this embodiment, the stability, moisture resistance and conductivity of lithium nitride are optimal, and the two-dimensional conductive material-coated lithium nitride as a lithium supplementing additive has the best gram-to-weight capacity and low raw material cost.
[0037] The thickness of the two-dimensional conductive material coating layer is 5-100nm, preferably, the thickness of the two-dimensional conductive material coating layer is 10-30nm. The thickness of the specific two-dimensional conductive material coating layer can be but not limited to 5nm, 7nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. The particle size of the lithium supplement additive is 5-60μm, preferably, the particle size of the lithium supplement additive is 5-10μm. The particle size of the specific lithium supplement additive can be but not limited to 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm. Within the range of the thickness of the two-dimensional conductive material coating layer and the particle size of the lithium supplement additive provided in the embodiment of the present application, the conductivity and stability of the lithium supplement additive can be optimized.
[0038] In the embodiment, the lithium supplement additive is placed in air with a relative humidity of 30% for 24 hours, and the content of lithium hydroxide is below 45%.
[0039] A second aspect of the present application provides a method for preparing a lithium supplement additive, comprising the following steps:
[0040] S10: providing metallic lithium;
[0041] S20: placing metallic lithium in a nitrogen atmosphere for calcination treatment, and then grinding to obtain lithium nitride.
[0042] The preparation method of the lithium supplement additive provided in the embodiment of the present application is to place the provided metal lithium in a nitrogen atmosphere for calcination treatment, and then grind it to obtain lithium nitride, which can be used as a lithium supplement additive. The preparation process is simple, easy to implement, and has low production cost. In addition, the lithium nitride prepared by the preparation method has good material stability and electrochemical properties, which is conducive to improving the first charging efficiency and overall electrochemical performance of the battery.
[0043] In step S20, the preparation method of lithium nitride includes the following steps: placing metallic lithium in a nitrogen atmosphere for calcination treatment, and then grinding to obtain lithium nitride.
[0044] In an embodiment, the calcination treatment is carried out in an inert gas, and the calcination treatment comprises the following steps: nitrogen and inert gas are introduced at a flow ratio of (1-9):1, and the temperature is increased to 180-900°C at a rate of 1-10°C / min, and kept warm for 5-24h, and then only nitrogen is introduced, and the temperature is reduced to 25°C at a rate of 1-50°C / min.
[0045] In some embodiments, the flow ratio of nitrogen to inert gas is (1-9): 1. Within the range of the flow ratio of nitrogen to inert gas provided in this embodiment, it is beneficial to improve the stability of the carburizing reaction and the experimental safety during the calcination process. Specifically, the flow ratio of nitrogen to inert gas can be, but is not limited to, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 7:3.
[0046] In some embodiments, the heating rate of the calcination process is 1-10°C / min. The heating rate can be adjusted according to the heating capacity of the equipment used. Within the range of the heating rate of the calcination process provided in the embodiment of the present application, it is conducive to uniform temperature in the furnace chamber, moderate time consumption, and can reduce the negative impact on the equipment. Specifically, the heating rate can be but not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min.
[0047] In some embodiments, the insulation temperature of the calcination treatment is 180-900°C, and the insulation time is 5-24h. Within the insulation temperature and insulation time range of the calcination treatment provided in the embodiment of the present application, it is beneficial to save energy consumption and reduce material costs. Specifically, the insulation temperature of the calcination treatment can be but not limited to 180°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, and the insulation time of the calcination treatment can be but not limited to 5h, 7h, 9h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0048] In some embodiments, the calcination pressure is 0.1-100 MPa. Within the range of the insulation temperature and pressure of the calcination provided in the embodiments of the present application, it is beneficial to reduce the requirements for equipment and reduce production costs. Specifically, the pressure of the calcination process can be, but is not limited to, 0.1 MPa, 0.5 MPa, 1 MPa, 10 MPa, 30 MPa, 50 MPa, 70 MPa, 90 MPa, 100 MPa.
[0049] In some embodiments, the cooling rate of the calcination treatment is 1-50°C / min. Since α-crystalline lithium nitride is a high-temperature stable crystalline phase, a temperature above 500K is conducive to the conversion of β-crystalline lithium nitride into α-crystalline lithium nitride; β-crystalline lithium nitride is a low-temperature stable crystalline phase, and a temperature below 300K is conducive to the stable existence of β-crystalline lithium nitride. Therefore, after high-temperature and high-pressure gas-liquid reaction nitriding, as the temperature decreases, α-crystalline lithium nitride is converted into β-crystalline lithium nitride, thereby controlling the cooling rate under high pressure to inhibit the conversion of α-crystalline lithium nitride into β-crystalline lithium nitride, thereby achieving the regulation of the mass ratio of β-crystalline lithium nitride and α-crystalline lithium nitride. Cooling within the range of the high-pressure environment and cooling rate provided in the embodiment of the present application can prepare α-crystalline and β-crystalline mixed-phase lithium nitride within the mass ratio range provided in the embodiment of the present application, so that the stability and lithium release capacity of the prepared α-crystalline and β-crystalline mixed-phase lithium nitride are the best, so the battery's first charging efficiency and overall electrochemical performance are optimized. Specifically, the cooling rate can be but is not limited to 1°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min.
[0050] In an embodiment, the preparation method of the lithium supplement additive further comprises the following steps:
[0051] S30: dispersing lithium nitride and a two-dimensional conductive material in a solvent to obtain a mixed solution, and drying the mixed solution to form a lithium supplement additive coated with the two-dimensional conductive material.
[0052] In step S30, the solvent includes at least one of N,N-dimethylformamide, tetrahydrofuran, n-hexane, and benzene. In a specific embodiment, the solvent may be N,N-dimethylformamide, tetrahydrofuran, or n-hexane.
[0053] In an embodiment, the conditions of the drying treatment include: a drying temperature of 30-100°C and a drying time of 6-10h. Within the range of the drying temperature and drying time provided in the present application, the solvent volatilization rate can be moderate, lithium nitride can be prevented from being enriched on the surface, and it is beneficial for the two-dimensional conductive material to form a uniform coating on the surface of lithium nitride. Specifically, the drying temperature can be but not limited to 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C. The drying time can be but not limited to 6h, 7h, 8h, 9h, 10h.
[0054] A third aspect of an embodiment of the present application provides a positive electrode material, which contains the electrode lithium supplement additive provided by the present application or the lithium supplement additive prepared by the preparation method provided by the present application.
[0055] The positive electrode material provided in the embodiments of the present application has good material stability and electrochemical properties, and can ensure that the voltage of the battery changes steadily during the charging process, because the positive electrode material contains the electrode lithium supplement additive provided in the present application or the lithium supplement additive prepared by the preparation method provided in the present application.
[0056] A fourth aspect of an embodiment of the present application provides a secondary battery, which contains the positive electrode material provided by the present application.
[0057] The secondary battery provided in the embodiment of the present application contains the positive electrode material provided in the present application. Therefore, during the first charging process, the lithium supplement additive contained in the electrode sheet of the present application can be used as a lithium source, and release lithium ions during the first charging process to achieve lithium supplementation, thereby maintaining the abundance of lithium ions in the battery system and improving the first charging efficiency and overall charge and discharge performance of the battery.
[0058] In the embodiment, a constant current and constant voltage charging method is adopted. When the charging voltage is 2.5-4.3V, the charging current is 0.1C, and the cut-off current is 0.01C, the number of lithium ions released from lithium nitride during the first cycle of charging of the secondary battery is 1.2-2.8.
[0059] The following describes the invention in conjunction with specific embodiments.
[0060] 1. Lithium supplement additive and preparation method thereof:
[0061] Example 1
[0062] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises pure α-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride core.
[0063] The preparation method of the lithium supplement additive of this embodiment comprises the following steps:
[0064] S10: providing metallic lithium;
[0065] S20: Place metallic lithium in a corundum boat and put it into a high-temperature and high-pressure reactor, and introduce argon at a flow rate of 300 mL / min for 30 minutes for exhaust; then introduce argon and nitrogen at a flow ratio of 70:30 mL / min, and increase the temperature to 800°C at a rate of 10°C / min. After keeping warm for 10 hours, increase the pressure in the furnace to 5 MPa, and cool it to 25°C at a rate of 40°C / min to obtain α-crystalline lithium nitride; finally, grind the α-crystalline lithium nitride to obtain pure α-crystalline lithium nitride particles.
[0066] S30: According to the mass ratio of α-crystalline lithium nitride particles to graphene being 30:1, α-crystalline lithium nitride particles and graphene are added into N,N-dimethylformamide and stirred at high speed for 60 minutes to obtain a mixed solution, and then the mixed solution is dried at a temperature of 50°C for 8 hours to obtain a lithium supplement additive in which graphene is coated on the surface of α-crystalline lithium nitride particles.
[0067] According to the test, the particle size of the α-crystalline lithium nitride particles is 1-8 μm, the thickness of the graphene coating layer is 10-30 nm, and the particle size of the lithium supplement additive is 1.01-8.05 μm.
[0068] Example 2
[0069] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises pure β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the β-crystalline lithium nitride core.
[0070] The preparation method of the lithium supplement additive of this embodiment is different from that of Embodiment 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 1° C. / min to obtain the lithium supplement additive in which graphene is coated on the surface of β-crystalline lithium nitride particles.
[0071] According to the test, the particle size of the β-crystalline lithium nitride particles is 1-8 μm, the thickness of the graphene coating layer is 10-30 nm, and the particle size of the lithium supplement additive is 1.01-8.05 μm.
[0072] Example 3
[0073] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive includes α-crystalline lithium nitride and β-crystalline lithium nitride.
[0074] The preparation method of the lithium supplement additive of this embodiment is different from that of embodiment 1 in that in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 32° C. / min to obtain a mixed crystalline phase of α-phase and β-phase lithium nitride.
[0075] According to the test, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8 μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 90:10.
[0076] Example 4
[0077] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0078] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 35° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0079] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 98:2.
[0080] Example 5
[0081] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0082] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 4 in that in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 32° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0083] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 90:10.
[0084] Example 6
[0085] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0086] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 28° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0087] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 80:20.
[0088] Example 7
[0089] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0090] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 25° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0091] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 70:30.
[0092] Example 8
[0093] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0094] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 18° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0095] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 10:90.
[0096] Example 9
[0097] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0098] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 13° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0099] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 8:92.
[0100] Example 10
[0101] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0102] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S20 of this embodiment, the temperature is lowered to 25° C. at a rate of 8° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0103] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 5:95.
[0104] Embodiment 11
[0105] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises α-crystalline lithium nitride and β-crystalline lithium nitride and a graphene coating layer bonded to the surface of the α-crystalline lithium nitride and the β-crystalline lithium nitride.
[0106] The preparation method of the lithium supplement additive of this embodiment is different from that of Example 1 in that, in step S10 of this embodiment, the temperature is lowered to 25° C. at a rate of 5° C. / min to obtain a lithium supplement additive in which graphene is coated on the surface of the α-crystalline lithium nitride and β-crystalline lithium nitride cores.
[0107] After testing, the particle size of the mixed crystalline phase lithium nitride of α-phase and β-phase is 1-8μm, the thickness of the graphene coating layer is 30nm, and the particle size of the lithium supplement additive is 1.01-8.05μm; in the mixed crystalline phase lithium nitride of α-phase and β-phase, the mass ratio of α-phase lithium nitride to β-phase lithium nitride is 2:98.
[0108] Comparative Example 1
[0109] This comparative example provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises lithium nitride particles.
[0110] The preparation method of the lithium supplement additive of this comparative example comprises the following steps:
[0111] S10: Place metallic lithium in a corundum boat and put it into a high-temperature and high-pressure reactor, and introduce argon gas at a flow rate of 300 mL / min for 30 minutes for exhaust; then introduce argon and nitrogen at a flow ratio of 70:30 mL / min, and increase the temperature to 800°C at a rate of 10°C / min. After keeping warm for 10 hours, naturally cool down to 25°C to obtain lithium nitride; finally, grind the lithium nitride to obtain lithium nitride particles.
[0112] According to the test, the particle size of lithium nitride particles is 1-8 μm, and the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride in the lithium nitride particles is 65:35.
[0113] Comparative Example 2
[0114] This comparative example provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive comprises lithium nitride particles and a graphene coating layer bonded to the surface of the lithium nitride.
[0115] The preparation method of the lithium supplement additive of this comparative example is different from that of comparative example 1 in that this comparative example further includes the following steps:
[0116] S20: According to the mass ratio of lithium nitride particles to graphene being 30:1, lithium nitride particles and graphene are added to N,N-dimethylformamide and stirred at high speed for 60 minutes to obtain a mixed solution, and then the mixed solution is dried at a temperature of 50°C for 8 hours to obtain a lithium supplement additive in which graphene is coated on the surface of the lithium nitride particles.
[0117] After testing, the particle size of lithium nitride particles is 1-8μm, the thickness of the graphene coating layer is 30nm, the particle size of the lithium supplement additive is 1.01-8.05μm, and the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride in the lithium nitride particles is 65:35.
[0118] 2. Related characteristics test analysis.
[0119] 1. Structural characterization of the lithium nitride core contained in the lithium supplement additive:
[0120] The lithium nitride cores provided in the above-mentioned Examples 1, 2, 4, 6 and 8 were subjected to X-ray diffraction analysis, and their XRD patterns are as follows: Figure 2 As shown. Figure 2 It can be seen that as the mass proportion of α-crystalline lithium nitride decreases and the mass proportion of β-crystalline lithium nitride increases, the intensity of the diffraction peak of the α-crystalline phase of lithium nitride decreases accordingly, and the intensity of the diffraction peak of the β-crystalline phase of lithium nitride increases accordingly.
[0121] 2. Lithium-ion battery electrochemical performance test analysis:
[0122] The lithium supplement additives provided in Example 3 and Comparative Example 1 were added to the LFP positive electrode, and the positive electrode slurry was prepared using N,N-dimethylformamide solvent. The battery was charged using a 0.1C constant current and constant voltage method, with a voltage range of 2.0-3.7V and a cut-off current of 0.01C, and the charge and discharge performance of the battery was tested.
[0123] Figure 3 The capacity-voltage diagram of the button cell assembled with lithium supplement additives provided in Example 5 and Comparative Example 2 is shown in FIG. Figure 3 It can be seen that in the mixed-phase lithium nitride coated with graphene provided in Example 5, the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride is 90:10, and it is used as a lithium supplement additive with more lithium detachment during the charging process, making the voltage change during the charging process relatively stable. This is because when the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride is 90:10, its stability is the best. In the lithium nitride provided in Comparative Example 2, the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride is 65:35. When used as a lithium supplement additive, severe polarization occurs at the beginning of the charging process. This is caused by the poor stability of lithium nitride itself. Therefore, within the range of the mass ratio of α-crystalline lithium nitride to β-crystalline lithium nitride provided in the embodiments of the present application, the stability of the α-crystalline and β-crystalline mixed-phase lithium nitride reaches the best, and the number of lithium ions detached from lithium nitride in the first cycle of charging reaches the maximum, which can maintain the voltage stable during the battery charging process.
[0124] Figure 4 The capacity-voltage diagram of the button cell without adding the lithium supplement additive and after adding the lithium supplement additive provided in Example 3 to the lithium iron phosphate positive electrode, from Figure 4 It can be seen that the positive electrode capacity performance of the lithium supplement additive provided in Example 3 of the present application is significantly improved. This is because the lithium ions of lithium nitride contained in the lithium supplement additive are transferred from the positive electrode to the negative electrode during the first cycle of charging, participating in the formation of the negative electrode SEI film and avoiding the loss of active lithium ions in the LFP material. Therefore, the lithium supplement additive can improve the capacity performance of the LFP battery.
[0125] Table 1
[0126]
[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium supplement additive, characterized in that: The lithium supplement additive includes lithium nitride, and the lithium nitride includes α-crystalline lithium nitride and β-crystalline lithium nitride; the mass ratio of the α-crystalline lithium nitride to the β-crystalline lithium nitride is (2-10): (90-98) or (70-98): (2-30).
2. The lithium supplement additive according to claim 1, characterized in that: The lithium supplement additive also includes a two-dimensional conductive material bonded to the surface of the lithium nitride.
3. The lithium supplement additive according to claim 2, characterized in that: The two-dimensional conductive material combined on the surface of the lithium nitride forms a two-dimensional conductive material coating layer that fully or partially covers the lithium nitride.
4. The lithium supplement additive according to claim 3, characterized in that: The two-dimensional conductive material includes at least one of graphene, graphyne, transition metal disulfide, and MXenes materials; Among them, the general formula of MXenes material is M n+1 X n T x , M includes at least one of Ti, Cr, Mo, V, Nb, Hf, Ta, and Sc; X includes at least one of C and N; T x Including OH - 、F - , O 2- NH4 + , at least one of NH3; n is 1-4; The transition metal disulfide includes at least one of MoS2, WS2, SnS2, and TiS2.
5. The lithium supplement additive according to claim 3 or 4, characterized in that: In the lithium supplement additive, the mass ratio of the lithium nitride to the two-dimensional conductive material coating layer is (9-99):
1.
6. The lithium supplement additive according to claim 3 or 4, characterized in that: The particle size of the lithium nitride is 0.1-50 μm; and / or The thickness of the two-dimensional conductive material coating layer is 5-100 nm; and / or The particle size of the coated lithium supplement additive is 5-60 μm.
7. The lithium supplement additive according to claim 3 or 4, characterized in that: The lithium supplement additive is placed in air with a humidity of 30% RH for 24 hours, and the content of lithium hydroxide is below 45%.
8. A method for preparing the lithium supplement additive according to any one of claims 1 to 7, characterized in that: The following steps are involved: Providing lithium metal; The metallic lithium is placed in a nitrogen atmosphere for calcination treatment, and then ground to obtain lithium nitride.
9. The preparation method according to claim 8, characterized in that: The calcination process comprises the following steps: The nitrogen and inert gas are introduced at a flow ratio of (1-9):1, and the temperature is increased to 180-900°C at a rate of 1-10°C / min, and kept for 5-24h, and then only nitrogen is introduced, and the temperature is reduced to 25°C at a rate of 1-50°C / min.
10. The preparation method according to claim 8 or 9, characterized in that: The preparation method further comprises: The lithium nitride and the two-dimensional conductive material are dispersed in a solvent to obtain a mixed solution, and the mixed solution is dried to form a lithium supplement additive coated with the two-dimensional conductive material.
11. A positive electrode material, characterized in that: The positive electrode material contains the lithium supplement additive described in any one of claims 1 to 7 and / or the lithium supplement additive prepared by the preparation method described in any one of claims 8 to 10.
12. A secondary battery, characterized in that: The secondary battery contains the positive electrode material according to claim 11.
13. The secondary battery according to claim 12, characterized in that: A constant current and constant voltage charging method is adopted. When the charging voltage is 2.5-4.3V, the charging current is 0.1C, and the cut-off current is 0.01C, during the first cycle charging of the secondary battery, the number of lithium ions released from the lithium nitride is 1.2-2.8.
Citation Information
Patent Citations
Lithium nitride composite material and preparation and application
CN111224077A
Lithium nitride particles and preparation method and preparation equipment thereof
CN113526474A